Upaya Guru BK Dalam Membina Akhlak di SMK Muhammadiyah 04 Medan - Umar Idris Dasopang; Saiful Akhyar Lubis; Irwan S. (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research aims to explore the efforts of Guidance and Counseling (BK) teachers in developing student morals at SMK Muhammadiyah 04 Medan, which is located in the Mesjid Raya Taqwa Block, Belawan Bahari, Medan Belawan, North Sumatra. This research uses qualitative methods with primary and secondary data. The results of the research show that the steps for moral development by guidance and counseling teachers include direct dialogue with students to solve problems, modeling by providing examples of good behavior, habituation by teaching commendable behavior, as well as providing advice and attention when students are affected by a negative environment. In addition, penalties are applied to violators of madrasa rules and regulations. Factors that influence moral development consist of internal factors, namely from the student’s personality such as lazy behavior, and external factors which include the community environment, family, and unmet needs. This research reveals the importance of a holistic approach in moral development that involves direct interaction, role models, and attention to factors that influence students from within and outside themselves.